Rationale, design, and organization of a randomized, controlled Trial Evaluating Cardiovascular Outcomes with Sitagliptin (TECOS) in patients with type 2 diabetes and established cardiovascular disease. - Green, J; Bethel, M; Paul, S; Ring, A; Ring, A; Kaufman, K; Shapiro, DR; Califf, R; Holman, R (2013)
Sitagliptin, an oral dipeptidyl peptidase-4 inhibitor, lowers blood glucose when administered as monotherapy or in combination with other antihyperglycemic agents. TECOS will evaluate the effects of adding sitagliptin to usual diabetes care on cardiovascular outcomes and clinical safety. TECOS is a pragmatic, academically run, multinational, randomized, double-blind, placebo-controlled, event-driven trial recruiting approximately 14,000 patients in 38 countries who have type 2 diabetes (T2DM), are at least 50 years old, have cardiovascular disease, and have an hemoglobin A1c value between 6.5% and 8.0%. Eligible participants will be receiving stable mono- or dual therapy with metformin, sulfonylurea, or pioglitazone, or insulin alone or in combination with metformin. Randomization is 1:1 to double-blind sitagliptin or matching placebo, in addition to existing therapy in a usual care setting. Follow-up occurs at 4-month intervals in year 1 and then twice yearly until 1300 confirmed primary end points have occurred. Glycemic equipoise between randomized groups is a desired aim. The primary composite cardiovascular endpoint is time to the first occurrence of cardiovascular death, nonfatal myocardial infarction, nonfatal stroke, or hospitalization for unstable angina, with cardiovascular events adjudicated by an independent committee blinded to study therapy. TECOS is a pragmatic-design cardiovascular outcome trial assessing the cardiovascular effects of sitagliptin when added to usual T2DM management.